ANALISIS PERBEDAAN KINERJA PERANGKAT DESA SEBELUM DAN SESUDAH MENGIKUTI PELATIHAN - Cahyono, Sugit (Jurnal Ilmu Administrasi dan Bisnis, 2020)
In realizing the implementation of village governance that is honest, fair, transparent, and following the wishes of the community, it is necessary that village officials who have competence in village governance. Training to increase the capacity of village officials in the field of village governance is very important to establish quality village officials. Researchers try to find out whether there are differences in the level of performance of village officials before and after attending training at the Yogyakarta Village Government Office. Based on research through different tests with paired sample t-test, there are significant differences in performance improvement, before and after training. It can be concluded that the village apparatus who have attended training at the Yogyakarta Village Government Office has improved performance.